PENINGKATAN PERFORMA SEPEDA MOTOR DENGAN VARIASI CDI PROGRAMMABLE THE IMPROVEMENT OF MOTORCYCLES PERFORMANCE USING CDI PROGRAMMABLE - Ibnu Siswanto; Yosep Efendi (Universitas Sarjanawiyata Tamansiswa, 2015)
The study aims to determine the engine performance characteristics of motorcycle that use CDI genuine and CDI programmable, and differences in performance characteristics of motorcycle engine that uses the CDI genuine and CDIÂ programmable. The study method used was experimental. The object of study was motorcycle 1 cylinder 125 cc. The equipment used to perform power measurement was dynotest motorcycle vehicle. Experiments conducted with the motorcycle still conditions in accordance with standard factory (no modification). The results showed that (1) Motorcycles with CDI Genuine produces the highest power 8HP obtained at 6542 RPM and the highest was 10.12 NM torque at 5085. While the RPM after it was replaced with CDI Programmable, peak power of 8.2 at 6556 RPM and torque of 10.33 in 4670. (2) ThereÂ was a difference in engine performance using CDI genuine and CDI Programmable. The highest power achieved in almost all variations of CDI Programmable, amounting 8,2HP. The highest torque was obtained by advancing the CDI Programmable Timing 2 degrees, itÂ 10,33Nm at 4670 RPM